Identifikasi Terong Tolaki Sebagai Sayuran Spesifik di Sulawesi Tenggara - Suharno, Suharno (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2010)
The total area of South East Sulawesi is 3.814.000 hectares, has several superior germplasm. One of that is small eggplant, its called Tolaki Eggplant. Tolaki eggplant growth in several districts in South East Sulawesi i.e: Konawe, South Konawe, Bombana, North Konawe, Kolaka, and North Kolaka. This eggplant has a popular in South East Sulawesi community, especially in Tolaki ethnics. The Tolaki ethnics, called to this eggplant is Palola. So far the identifications to this eggplant not implemented yet. Based on the conditions, need to identifications to Tolaki eggplant. Research objectives to identifications of several aspects ie: plant form, flower form, fruits form, and resistance in storage. Research conduct in Puuwatu sub-district, Kendari City from March to November 2009. The research results indicated that Tolaki eggplant height is 40-60 cm, the fruits from is small and oval, the skin of fruits is grey strip and potential to storage on 6 days in room temperature.